Intrusion prevention and active response : deploying network and host IPS - Rash, Michael (Syngress Pub., 2005)
Within a year of the infamous "Intrusion Detection is Dead" report by Gartner, we started seeing Intrusion Prevention System (IPS) products that actually worked in the real world. Security professionals are going to be approaching management for funding in the next year or two to procure intrusion prevention devices, especially Intelligent switches from 3Com (TippingPoint), as well as host-based intrusion prevention solutions like Cisco Security Agent, Platform Logic, Ozone or CrossTec. Both managers and security technologists face a pressing need to get up to speed, and fast, on the commercia